Does Better Information Curb Customs Fraud? - Cyril Chalendard; Alice Duhaut; Ana Margarida Fernandes; Aaditya Mattoo; Gael Raballand; Bob Rijkers (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper examines how providing better information to customs inspectors and monitoring their actions affects tax revenue and fraud detection in Madagascar. First, an instrumental variables strategy is used to show that transaction-specific, third-party valuation advice on a subset of high-risk import declarations increases fraud findings by 21.7 percentage points and tax collection by 5.2 percentage points. Second, a randomized control trial is conducted in which a subset of high-risk declarations is selected to receive detailed risk comments and another subset is explicitly tagged for ex-post monitoring. For declarations not subject to third-party valuation advice, detailed comments increase reporting of fraud by 3.1 percentage points and improve tax yield by 1 percentage point. However, valuation advice and detailed comments have a significantly smaller impact on revenue when potential tax losses and opportunities for graft are large. Monitoring induces inspectors to scan more shipments but does not result in the detection of more fraud or the collection of additional revenue. Better information thus helps curb customs fraud, but its effectiveness appears compromised by corruption.
Keywords: D73; F14; H26; K42; 330; tariff evasion; tax enforcement; third-party information; performance monitoring; risk management; information provision; randomized control trial